The Implementation of Patient Safety by Nurses Based on Work Design - Sri Hananto Ponco Nugroho; Puguh Widiyanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Patient safety incidents are increasing and can result in death. Hospitals are required to provide quality and safe service. Thus, making policies to improve the quality of patient safety based on evidence is very important. This study aimed to determine the relationship between work design and the implementation of patient safety by the nurses. The design of this research was a descriptive correlation with a cross-sectional approach. The sampling technique used purposive sampling with a total sample of 56 nurses in the Inpatient Room of a hospital in Temanggung Regency. The data was collected through a work design questionnaire instrument and digital instrument/ calculators obtained through observation. Then, the data were analyzed by the chi-square test. The results showed that there was a significant relationship between work design and the implementation of patient safety by the nurses (p = 0.000). Nurses who had a good perception of work design were found to carry out patient safety well. It is suggested that the hospital management needs to support the implementation of patient safety through the work design of the head of the room by compiling standard operational procedures. The head of the room needs to improve the implementation of work design so that all nurses can perform patient safety according to standards.